If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y in (-oo:+oo)
(5/2)*y-y-(3/1) = 0
(5/2)*y-y-3 = 0
3/2*y-3 = 0 // + 3
3/2*y = 3 // : 3/2
y = 3/3/2
y = 2
y = 2
| m/60=24 | | -16.47=2.4x-4.5-0.3x | | sin(3x+20)=-cos(x+10) | | 20x^2-5=2 | | 1.84=-1.1r+5.7r | | 12/25=x/75 | | -6(m)=-6(8+2n) | | x/23=39 | | -8x+5(4x+4)=164 | | Axy=c | | -319=9(1-9p)-4 | | X-d=a | | 3z-2y=12 | | Z+5y=10 | | m/60=26 | | 134=9n+2(4n-1) | | Ln^2=11 | | 2z+y=12 | | 13/17=v/10 | | sen3x=1/2 | | 7x-5(-7x+6)=-240 | | 4x+3y-z=17 | | 6z-2y=8 | | -5(1+9v)=310 | | 10x+30=20x+20 | | 6x^2+35=68 | | 9z-12y=9 | | -504=3(11x+4)+10x | | 3z-4y=3 | | -7(6)(-1)= | | 35k=1925 | | 5x-57-2x=63 |